PENGGUNAAN MODEL MIND MAPPING UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Hartanti, Hartanti; Marli, Suhardi; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to improving learning outcomes of students in Social Science by using the model of Mind Mapping for fifth grade at Nyandung Elementary School. This research is action research class (PTK) that consist of 3 cycles. Which in each cycles consist of planning, implementation, observation, and reflection. The subject of this research is the students of fifth grade at Nyandung Elementary School. Data technique collection of this research are using participation technique, observation, and analysis of documents. Techniques used are observation and scrutiny of documents, data collection tool is an observation sheet and document scrutiny sheet. The outcomes learning at the first cycle got 61 % or 17 by 27 of students could through the minimum score. At the second cycle got 71 % or 20 by 27 of students could through the minimum score. At the third cycle got 82 % or 23 by 27 of students could through the minimum score. It has showed that using the model of Mind Mapping for fifth grade at Nyandung Elementary School could improved learning outcome in Social Science. Keywords: Mind Mapping, Learning Outcomes